2021
DOI: 10.1002/adsc.202100069
|View full text |Cite
|
Sign up to set email alerts
|

Indene Derived Phosphorus‐Thioether Ligands for the Ir‐Catalyzed Asymmetric Hydrogenation of Olefins with Diverse Substitution Patterns and Different Functional Groups

Abstract: A family of phosphite/phosphinite‐thioether ligands have been tested in the Ir‐catalyzed asymmetric hydrogenation of a range of olefins (50 substrates in total). The presented ligands are synthesized in three steps from cheap indene and they are air‐stable solids. Their modular architecture has been crucial to maximize the catalytic performance for each type of substrate. Improving most Ir‐catalysts reported so far, this ligand family presents a broader substrate scope, covering different substitution patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 136 publications
1
10
0
Order By: Relevance
“…In particular, we considered the hydrogenation of α,α-unsaturated exocyclic enones and α,α-unsaturated lactones and lactams, since the reduced products of these olefins are encountered in natural products and drugs . These substrates suffer from the same ring size limitation that was discussed for exocyclic olefins without a neighboring polar group . In our case, however, the hydrogenation of the exocyclic enones S49 and S50 using 4a proceeded with high enantioselectivities (up to 97%), comparable to the best ones, regardless of the size of the ring.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…In particular, we considered the hydrogenation of α,α-unsaturated exocyclic enones and α,α-unsaturated lactones and lactams, since the reduced products of these olefins are encountered in natural products and drugs . These substrates suffer from the same ring size limitation that was discussed for exocyclic olefins without a neighboring polar group . In our case, however, the hydrogenation of the exocyclic enones S49 and S50 using 4a proceeded with high enantioselectivities (up to 97%), comparable to the best ones, regardless of the size of the ring.…”
Section: Resultsmentioning
confidence: 72%
“…Even for the most studied trisubstituted olefins, there is still room for improvement. For example, the reduction of the so-called purely alkyl-trisubstituted olefins, those without functional groups or aryl substituents, has been achieved in very few cases and the effectiveness for exocyclic substrates needs to be improved . For tetrasubstituted olefins, only a few specific Ir-catalysts have provided high performance for certain substrates, with variable enantioselectivity and low functional group tolerance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with the substituent-based data extraction in methyl (Z)-2-acetamido-3-phenylacrylate (Figure 4d), which demonstrated that the hierarchical learning approach can apply to additional structural evaluation methods.U sing Morgan fingerprints-based data extraction, we also tested the hierarchical learning approach with out-of-sample examples from an ew AHO reference in 2021. [48] Consistently,t he hierarchical learning model led to improved predictive performance as compared to naive training and training with target substrate set (Table S8 and Figure S13-S15).…”
Section: Methodsmentioning
confidence: 54%
“…Aside, olefin migration prior to hydrogenation can potentially lead to the reduction of unreactive olefins. Hydrogenations using deuterium gas are sometimes reported to give substantial amounts of deuterium incorporation in the allylic position, which is suggested to occur as a consequence of olefin migration. ,, Despite that other pathways can also lead to the observed deuterium scrambling, the migration of olefins under hydrogenative conditions remains a topic for further study …”
Section: Outlook and Opportunitiesmentioning
confidence: 99%